The specific energy absorption of local wood subjected to quasi-static loading - Mohd Khairir, Ismail; Md Radzai , Said; Mohd Firdaus, Zakaria (2011)
Abstract—An experimental investigation was performed to obtain specific energy absorbed of Malaysia local wood. Eleven species of wood were chosen which are, Nyatoh, Merbau, Meranti Putih, Kelapa Sawit, Kempas, Jati, Chengal,Meranti Merah, Balau Cina, Balau Merah, and Kapur . The wood in compressed quasi-statically usingUniversal Testing Machine to obtain the material mechanical properties. Specimens were loaded in axial, circumferential and radial directions. Kink-band phenomena was observed and studied. The deformation mode and the load-displacement curve for axial, circumferential and radial compression of local woods, the highest value of energy absorption and kink-band phenomena as well as its effect on energy absorption were determined and discussed in this paper.